DYNAMIC CONDITIONS FOR THE DEVELOPMENT OF INTELLECTUAL POSSIBILITIES OF TEACHERS. (Conference Zone, 2021)
This article describes the educational system, pedagogical methods used to improve the intellectual abilities of learners, games, and their importance.